#### Answer

$f(-0.5)=-8$

#### Work Step by Step

To find $f(-0.5)$, substitute $-0.5$ to $x$ in $f(x)$ to obtain:
$f(x) =-2x^2+3x-6
\\f(-0.5)=-2(-0.5)^2+3(-0.5)-6
\\f(-0.5)=-2(0.25)-1.5-6
\\f(-0.5)=-0.5-1.5-6
\\f(-0.5)=-2-6
\\f(-0.5)=-8$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$f(-0.5)=-8$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.